Rekonstruksi Pertunjukan Séndêlan Madura - ahmad faisal, ahmad faisah; Helmi, m (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
The Séndêlan performance is an attempt to reconstruct a traditional performance that is almost extinct. Although basically it is part of traditional performing arts such as Sandur, Kejung and Ludruk. At first glance, Séndêlan is a reciprocal rhyme that contains innuendos. Séndêlan in Sandur performances is an important part of the actor's dialogues. However, Séndêlan is not only done in the performance area. Séndêlan is also practiced by Madurese people in everyday life. For example, Séndêlan is done at the opening of a dialogue about engagement, or proposing to a woman. Seduction. Etc. Séndêlan is often interpreted as a type of old poetry consisting of four lines with ab-ab rhyme. The first and second lines are called sampiran or hanging, the third and fourth lines are called content, meaning, purpose, or theme. However, Séndêlan is identical to the rhymes that are sung or sung in performances. Séndêlan performance activities are an effort to reconstruct, preserve and maintain traditional values. Especially for the younger generation. And this activity can be categorized as successful because it can attract the interest of the younger generation and children to get involved in the Séndêlan Performance activities.